2023
DOI: 10.1186/s40798-023-00582-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a High-Volume 7-Week Pectoralis Muscle Stretching Training on Muscle Function and Muscle Stiffness

Abstract: Background There is evidence that high-volume static stretching training of the lower limbs can increase the range of motion (ROM) while decreasing muscles stiffness. However, to date, there is no evidence on the effects of upper limb stretching training or its effect mechanism. Therefore, this study aimed to investigate the effects of a comprehensive 7-week static stretching training program of the pectoralis major muscle (PMa) on glenohumeral joint ROM, muscle force, and muscle stiffness. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…The meta-analytical approaches might be seen as a supplementation to quantify results. Although some short duration stretching interventions sufficiently increased maximal strength ( Nelson et al, 2012 ; Mizuno 2019 ), consistent stretch-induced strength and muscle size increases were reported after longer stretching durations (≥10 min per session) ( Chen et al, 2011 ; Wohlann et al, 2023 ; Wohlann et al, 2024 , Warneke et al, 2022a , Reiner et al, 2023 ; Warneke et al, 2022). However, stretching durations of the included studies primarily used short stretching durations of a few minutes.…”
Section: Limitationsmentioning
confidence: 80%
“…The meta-analytical approaches might be seen as a supplementation to quantify results. Although some short duration stretching interventions sufficiently increased maximal strength ( Nelson et al, 2012 ; Mizuno 2019 ), consistent stretch-induced strength and muscle size increases were reported after longer stretching durations (≥10 min per session) ( Chen et al, 2011 ; Wohlann et al, 2023 ; Wohlann et al, 2024 , Warneke et al, 2022a , Reiner et al, 2023 ; Warneke et al, 2022). However, stretching durations of the included studies primarily used short stretching durations of a few minutes.…”
Section: Limitationsmentioning
confidence: 80%
“…Indeed, the applied stretching stimulus of the pectoralis muscles is enough to induce local changes in ROM (i.e., shoulder extension) as have been shown in a previous study (Reiner et al, 2023).…”
Section: Discussionmentioning
confidence: 51%
“…Assuming a dose–response relationship, recent research enhanced the stretching duration up to 2 h per day for 6 weeks [ 30 ], showing highly consistent results in the plantar flexors. Similarly, upper-body-muscle static stretching induced pectoralis muscle hypertrophy [ 17 ] and strength increases [ 17 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the plantar flexors can be considered a comparatively small muscle group with comparably low impact on multi-articular, complex (athletic) movements [ 15 , 16 ]. While Wohlann et al [ 17 ], Ikeda and Ryushi [ 18 ] and Chen et al [ 19 ] reported stretch-induced strength increases in the thigh muscles, Reiner et al [ 20 ], Warneke et al [ 21 ] and Wohlann et al [ 17 ] showed transferability to the upper body. Wohlann et al [ 17 ] pointed out that 15 min of supervised stretching has the potential to substitute high-intensity pectoralis resistance training.…”
Section: Introductionmentioning
confidence: 99%